Effects of different microplastics on the physicochemical properties and microbial diversity of rice rhizosphere soil - Sheng Lai; Sheng Lai; Sheng Lai; Cunzhong Fan; Ping Yang; Ping Yang; Yuanyuan Fang; Yuanyuan Fang; Lanting Zhang; Lanting Zhang; Minfei Jian; Guofei Dai; et al. (Frontiers in Microbiology)
Biodegradable plastics, as alternatives to conventional waste plastics, are increasingly applied across various fields. However, the ecological risks associated with the widespread use of biodegradable plastics remain unclear. Additionally, biodegradable plastics tend to age in the environment, leading to changes in their physicochemical properties. The ecological risks brought by the aging of microplastics have also been scarcely studied. In this study, we selected conventional microplastics (PE-MPs), biodegradable microplastics (PLA-MPs), and aged biodegradable microplastics (aging-PLA-MPs) to explore their effects on the rhizosphere soil environment of rice. The results showed that microplastics reduced the soil N and P content, with PE slightly increasing the DOC content, while PLA and aging-PLA significantly increased DOC by 21.13 and 24.04%, respectively. Microplastics also decreased soil enzyme activity, with aging-PLA having a somewhat stimulatory effect on enzyme activity compared to PLA. Furthermore, microplastics reduced the soil bacterial diversity index and altered the community structure of dominant bacterial species, with DOC content and FDA hydrolase being the main factors influencing the soil bacterial community. Bacteria were most sensitive to PLA, and the stability of the bacterial microbial network structure decreased, although aging reduced the negative impact of PLA on the bacterial community. This study contributes to our understanding of the ecological risks posed by biodegradable plastics and their aging processes on the environment.